Biology Needs Evolutionary Software Tools: Let's Build Them Right. (23rd April 2018) - Nekrutenko, Anton; Team, Galaxy; Goecks, Jeremy; Taylor, James; Blankenberg, Daniel
Abstract: Research in population genetics and evolutionary biology has always provided a computational backbone for life sciences as a whole. Today evolutionary and population biology reasoning are essential for interpretation of large complex datasets that are characteristic of all domains of today's life sciences ranging from cancer biology to microbial ecology. This situation makes algorithms and software tools developed by our community more important than ever before. This means that we, developers of software tool for molecular evolutionary analyses, now have a shared responsibility to make these tools accessible using modern technological developments as well as provide adequate documentation and training.